Optimalisasi Sukuk sebagai Instrumen untuk Mengakselerasi Investasi Syariah dalam Pembangunan Ekonomi di Indonesia - Khofaria Amini Hutapea; Hesi Eka Puteri (ARZUSIN, 2026)
The optimization of sukuk as an Islamic investment instrument in supporting economic development has received attention in various previous studies. However, studies that specifically integrate analyses of the role of sukuk, constraints on its optimization, and development strategies within a single research framework remain limited. This study aims to analyze the role of sukuk as an Islamic investment instrument in accelerating Indonesia’s economic development, identify various constraints encountered, and formulate optimization strategies. This study employed a qualitative approach with a literature research or library research design. Data sources were obtained through documentation studies of books, journal articles, laws and regulations, fatwas of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI), as well as official publications from the government and relevant institutions selected purposively based on their relevance to the research focus. The data were analyzed using an interactive analysis model that includes data condensation, data display, and conclusion drawing and verification. The results show that sukuk plays a strategic role as an instrument for development financing, strengthening the Islamic capital market, and increasing investment in the real sector. Nevertheless, the optimization of sukuk still faces constraints in the form of low Islamic financial literacy, limited investor participation, suboptimal product innovation, and the need to strengthen regulation. These findings reinforce studies in Islamic economics, particularly regarding the optimization of sukuk as an Islamic investment instrument in supporting economic development. The conclusion of this study emphasizes the importance of improving Islamic financial literacy, expanding the investor base, product innovation, and strengthening regulation to enhance the effectiveness of sukuk development in Indonesia. The implications of the study include theoretical contributions to the development of Islamic economics literature and practical implications for the government, regulators, and Islamic financial institutions in formulating more effective sukuk development policies.